The Progress of the Prevention and Treatment of Vitamin D to Tuberculosis - Cai, Li; Wang, Gaoming; Zhang, Peijun; Hu, Xinyi; Zhang, Hao; Wang, Fan; Tong, Yeqing (Frontiers in Nutrition, 2022)
The progressions of a number of lung diseases, including acute lung injury, cystic fibrosis, asthma, chronic obstructive pulmonary disease, pneumonia and tuberculosis (TB) are found to be highly associated with inflammatory responses. As a signaling nutrient, Vitamin D modulates the activities of dendritic cells, monocytes/macrophages, T and B cells, and tissue epithelial cells in the body to induce inflammatory responses and boost immune functions. Given the high prevalence of vitamin D deficiency among pulmonary insufficiency and inflammation-related cases, researchers indicated vitamin D supplementation could have a potential role in the prevention and treatment of lung disease, especially tuberculosis. In this paper, we reviewed published studies on the role of vitamin D in the prevention and treatment of tuberculosis. The paper identified vitamin D’s potential as an adjunctive therapy and demonstrated its safety so as to provide an impetus for further studies and clinical applications.